2015
DOI: 10.3389/fnhum.2015.00476
|View full text |Cite
|
Sign up to set email alerts
|

Immunological findings in psychotic syndromes: a tertiary care hospital's CSF sample of 180 patients

Abstract: Immunological mechanisms and therapy approaches in psychotic syndromes were recently supported by the discovery of autoantibody-associated limbic and non-limbic encephalitis. However, how clinical diagnostic procedures in psychiatry should be adapted to these new insights is still unclear. In this study, we analyzed the cerebrospinal fluid (CSF) and neuroimmunological alterations and their association with cerebral MRI (cMRI) and electroencephalographic (EEG) findings. From 2006 to 2013, we acquired 180 CSF sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
114
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 31 publications
(47 reference statements)
14
114
0
Order By: Relevance
“…To date, four studies that have screened individuals with schizophrenia spectrum disorders for the aforementioned antibodies have included CSF findings [10, 16, 29, 40], and three have yielded positive results [10, 16, 40]. The methodological details of these studies are outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…To date, four studies that have screened individuals with schizophrenia spectrum disorders for the aforementioned antibodies have included CSF findings [10, 16, 29, 40], and three have yielded positive results [10, 16, 40]. The methodological details of these studies are outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…IgGs against the GluN1a subunit were described in two first episode catatonic schizophrenic patients (probably misdiagnosed NMDA-R encephalitis), while two other paranoid schizophrenia patients presented IgGs against GluN1a/2b, in lower titers, which declined during remission also shown in other studies [115,141,145]. Curiously, only the two patients with anti-GluN1 IgG autoantibodies presented IgG positive titers in CSF, a controversial result based on the 3.2% reactivity to neuronal surface antigens in CSF found in a psychotic disorder cohort (0.8% to NMDA-R and 2.4% to VGKC complex) [144]. Another study showed GluN1 IgG autoantibodies in 5 out of 43 children with a first episode of acute psychosis, screened by a more objective variety of the CBA using flow cytometry [160].…”
Section: Psychotic Disordersmentioning
confidence: 70%
“…The frequency of autoantibodies to NMDA-R and VGKC complex in different studies ranged from 0% to 10% in cohorts of first-episode psychosis or schizophrenia [38,122,144,159,161,162]. Nevertheless, the results are controversial, since a number of other studies did not find autoantibodies in neuropsychiatric cohorts [146,159,162,163] or not specific to the disease [45,122].…”
Section: Psychotic Disordersmentioning
confidence: 99%
See 2 more Smart Citations